Lived Experiences of Junior High School Teachers During the Covid-19 Pandemic - Flordeliza Addatu; Darwin Caronan; Juliet Addatu; Ethel Joyce Layus; Annaliza Bunagan; Darin Jan Tindowen (PT FORMOSA CENDEKIA GLOBAL, 2023)
The presence of different modalities or flexible learning became the current trend in education because of the Covid 19 pandemic. This is to address the needs of the learners without delimiting the objectives and necessary skills even amid pandemic. This study was conducted to explore the lived experiences of teachers during the Covid 19 pandemic upon the implementation of flexible learning. Phenomenological interpretative research utilizing an in-depth one-on-one interview method was employed. 10 teachers in the Junior High School Department were considered participants of the study. The result reveals that teachers experienced both positive and negative towards the implementation of flexible learning. Most of the teachers enhanced their skills thru the conducted seminars and webinars. However, teachers struggled in communicating with parents and students especially addressing the non-submission of outputs. This study concludes that even during pandemic, teachers were able to cope up with the challenges and hindrances in the teaching and learning process.